The use of assembly PCR for cloning of a malarial epitope into mycobacterium smegmatis - Nor, Norazmi Mohd; Z.F., Zainuddin; J, Dale (1999)
Mycobacterium bovis bacille Calmette Geurin (BCG) has been suggested to be an attractive vehicle for the delivery of various vaccine candidates,including those for malaria. However,despite possessing strong immunoadjuvant properties, recombinant BCG containing these malarial epitopes fail to elicit significant specific immunogenicity in mice.One possibility for this may be the codon bias between these organisms: mycobacteria is G:C rich while plasmodia is A:T rich. To test this hypothesis, we cloned the candidate malarial epitope, the C-terminus of Plasmodium falciparum merozoite surface protein-1(MSP-lC) using assembly PCR into Mycobacterium smegmatis. This technique involved the generation of the full 300bp fragment from 18, overlapping 40bp oligonucleotides designed in favour of mycobacteria codon usage. The fragment was cloned into the M.leprae l8kDa gene driven by the mycobacterial hsp60 promoter in a plasmid designated pUS937. The whole hsp60/18kDa/MSP-1C cassette was then cloned into a mycobacteriai replicative plasmid, pUS972, to produce pUS1754. A clone (pUS1758) containing the 'native' homologue of MSP-lC generated by PCR of genomic P. falciparum DNA was also constructed. Western blot analyses using an antibody against the 18kDa epitope showed that recombinants containing pUS 1754 had approximately 100-fold higher expression levels than those containing pUS1758. Two additional clones containing the 'native' MSP-lC also showed low level expression as compared to the clone containing pUS1754. Thus overcoming codon bias for selected vaccine candidates may be important in increasing the level of their expression and hence could improve the immunogenecity of such epitopes cloned into mycobacteria.